2020
DOI: 10.1029/2020gl087452
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of a Debris Slide From the Joint Analysis of UAVSAR and LiDAR Data

Abstract: Landslide rheology governs the deformation and flow behavior of sliding masses. As rheology strongly varies as a function of the composition and environment of landslides, a wide range of viscosities have been suggested based on very limited experimental or observational constraints. Here, we introduce a novel method to quantify the landslide rheology from remote sensing data. We focus on an ideal natural laboratory, the Slumgullion landslide, Colorado, which has moved at tens of millimeters per day for centur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The classic Bingham flow model, with the presence of a yield surface at which flow terminates, may not be suitable for analyzing the entire landslide. Nonetheless, the Bingham flow model can be used to quantify the intrinsic viscosity of the frontal toe area 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The classic Bingham flow model, with the presence of a yield surface at which flow terminates, may not be suitable for analyzing the entire landslide. Nonetheless, the Bingham flow model can be used to quantify the intrinsic viscosity of the frontal toe area 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [45] used the time-series deformation derived via the POT method to obtain the kinematic parameters (i.e., linear and seasonal velocities), and revealed the relationships between landslide motion, geological, and meteorological conditions. Subsequently, Hu et al [46][47][48] also studied the landslide motion and internal structure using the POT and D-InSAR methods. These studies have demonstrated the capacity of SAR to measure landslide deformations and understand the mechanisms affecting their motion.…”
Section: The Slumgullion Landslidementioning
confidence: 99%
“…Free-surface flows of fluids that have a yield stress are common in the environment. Examples include lava flows, fluidised mine tailings, mud slides and avalanches (Coussot & Proust 1996;Fink & Griffiths 1998;Hu & Bürgmann 2020). Often these flows interact with topography and obstructions such as trees and constructed barriers (Tai et al 2001;Barberi et al 2003;Dietterich et al 2015;Bernabeu, Saramito & Harris 2018;Chevrel et al 2019).…”
Section: Introductionmentioning
confidence: 99%